In search of the Paleo-Amazon river connection between the northern South America and the Pacific Ocean (2018)
It is thought that the western part of the Paleo-Amazon River had an east-west flow between the Cretaceous and the Miocene time. This drainage configuration allowed the transport of sediments from the north and central South America to the western part of the continent. In this study U/Pb, trace elements and typological analyses for detrital zircons from Ecuador showed evidence of this flow direction. Furthermore, the Ecuador zircon ages were compared with Gorgona and Galapagos zircon ages that were reported in a previous study. From this, it exists a possible relation between zircons transported by active river sediments and detrital zircons found in Gorgona Island sands. Finally, it is proposed a possible origin for zircons found in Galapagos sands using the Paleo-Amazon River hypothesis.